Predicting rice pesticide fate and transport following foliage application by an updated PCPF-1 model. (1st January 2021) - Tu, Le Hoang; Boulange, Julien; Phong, Thai Khanh; Thuyet, Dang Quoc; Watanabe, Hirozumi; Takagi, Kazuhiro
Abstract: The Pesticide Concentration in Paddy Field (PCPF-1) model has been successfully used to predict the fate and transport of granular pesticides applied to the paddy fields. However, it is not applicable for pesticides in foliar formulation while previous studies have reported that foliar application may increase the risks of rice pesticide contamination to the aquatic environment due to pesticide wash-off from rice foliage. In this study, we developed and added a foliar application module into the PCPF-1 model to improve its versatility regarding pesticide application methods. In addition, some processes of the original model such as photodegradation were simplified. The updated model was then validated with data from previous studies. Critical parameters of the model were calibrated using the Sequential Uncertainty Fitting version 2 (SUFI-2) algorithm. The calibrated model simulated pesticide dissipation trend and concentrations with moderate accuracy in the two paddy compartments including rice foliage and paddy water. The accuracy of the predicted soil concentrations could not be evaluated since no observed data were available. Although the p-factor and r-factor obtained using the SUFI2 algorithm indicated that the uncertainty encompassed in the predicted concentrations was rather high, the daily predicted pesticide concentrations in rice foliage and paddy water were satisfactory based on the NSE values (0.36–0.89). The updated PCPF-1 model is a flexible tool for the environmental risk assessment of pesticide losses and the evaluation of agricultural management practices for mitigating pesticide pollution associated with rice production. Graphical abstract: Image 1 Highlights: An extended version of PCPF-1 model was developed for foliar application method. The model was validated with data obtained under Japanese paddy field conditions. The SUFI2 algorithm can help to improve the accuracy of the PCPF-1 model simulation. The fate and transport of tricyclazole in rice foliage and paddy water at lysimeter scale were successfully simulated.